Perbedaan Gender dan Sikap terhadap Peran Pekerjaan-Keluarga: Implikasinya pada Perkembangan Karir Wanita - Jati Waskito; Irmawati Irmawati (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Surakarta, 2007)
This study attempts to examine wether the attitude to work an family roles ofprofessional men and women in Surakarta, follow the pattern suggested by adultdevelopment theories. The results indicate that there were no significant different betweenthe scroes of men and women participants in work role during their life cycle.Nevertheless, there are some different role in the family (parental, marital, and homemaker) a long their life cycle